Analysis of the Security System at Class II A Kupang Correctional Institution in Preventing Inmate Escape Cases - Putri Aliman, Shalsabilah; Amalo, Heryanto; Sonbait, Sigit Prabowo (JURNAL HUKUM SEHASEN, 2026)
This study examines the implementation and effectiveness of the security system at Class IIA Kupang Correctional Institution in preventing inmate escape cases. Using an empirical juridical approach with a qualitative descriptive method, the research analyzes the application of security regulations in practice and identifies factors influencing their effectiveness. The findings reveal that the security system has been implemented through three primary mechanisms: static security, dynamic security, and procedural security. These measures have been carried out in accordance with Law Number 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights Number 33 of 2015 concerning Security in Correctional Institutions and Detention Centers. Physical security arrangements, dynamic supervision by officers, and the implementation of standard operating procedures (SOPs) have formally functioned as required by applicable regulations. However, despite the availability of a structured regulatory framework and established security mechanisms, the effectiveness of the system in practice remains constrained. The study indicates that operational challenges limit the optimal prevention of inmate escapes. The effectiveness of the security system is significantly influenced by several interconnected factors, including limited human resources, inadequate security facilities and infrastructure, and the high density of inmates. These factors collectively affect the overall security environment and hinder the full realization of preventive objectives. In conclusion, although the security system at Class IIA Kupang Correctional Institution is normatively well-designed, its practical implementation has not yet achieved optimal effectiveness in preventing inmate escapes.